Respiratory Muscle Function Tests and Diaphragm Ultrasound Predict Nocturnal Hypoventilation in Slowly Progressive Myopathies - Spiesshoefer, Jens; Lutter, Riccarda; Kabitz, Hans-Joachim; Henke, Carolin; Herkenrath, Simon; Randerath, Winfried; Young, Peter; Dreher, Michael; Görlich, Dennis; Boentert, Matthias (Frontiers in Neurology, 2021)
Introduction: In slowly progressive myopathies, diaphragm weakness early manifests through sleep-related hypoventilation as reflected by nocturnal hypercapnia. This study investigated whether daytime tests of respiratory muscle function and diaphragm ultrasound predict hypercapnia during sleep. Methods: Twenty-seven patients with genetic myopathies (myotonic dystrophy type 1 and 2, late-onset Pompe disease, facioscapulohumeral dystrophy; 48 ± 11 years) underwent overnight transcutaneous capnometry, spirometry, measurement of mouth occlusion pressures, and diaphragm ultrasound. Results: Sixteen out of 27 patients showed nocturnal hypercapnia (peak ptcCO2 ≥ 50 mmHg for ≥ 30 min or increase in ptcCO2 by 10 mmHg or more from the baseline value). In these patients, forced vital capacity (FVC; % predicted) and maximum inspiratory pressure (MIP; % of lower limit or normal or LLN) were significantly reduced compared to normocapnic individuals. Nocturnal hypercapnia was predicted by reduction in FVC of <60% [sensitivity, 1.0; area under the curve (AUC), 0.82] and MIP (%LLN) <120% (sensitivity, 0.83; AUC, 0.84), the latter reflecting that in patients with neuromuscular disease, pretest likelihood of abnormality is per se higher than in healthy subjects. Diaphragm excursion velocity during a sniff maneuver excluded nocturnal hypercapnia with high sensitivity (0.90) using a cutoff of 8.0 cm/s. Conclusion: In slowly progressive myopathies, nocturnal hypercapnia is predicted by FVC <60% or MIP <120% (LLN). As a novelty, nocturnal hypercapnia can be excluded with acceptable sensitivity by diaphragm excursion velocity >8.0 cm/s on diaphragm ultrasound.